The Epidemiology and Burden of Influenza B/Victoria and B/Yamagata Lineages in Kenya, 2012–2016. (30th September 2019) - Emukule, Gideon O; Otiato, Fredrick; Nyawanda, Bryan O; Otieno, Nancy A; Ochieng, Caroline A; Ndegwa, Linus K; Muturi, Peter; Bigogo, Godfrey; Verani, Jennifer R; Muthoka, Philip M; Hunsperger, Elizabeth; Chaves, Sandra S
Abstract: Background: The impact of influenza B virus circulation in Sub-Saharan Africa is not well described. Methods: We analyzed data from acute respiratory illness (ARI) in Kenya. We assessed clinical features and age-specific hospitalization and outpatient visit rates by person-years for influenza B/Victoria and B/Yamagata and the extent to which circulating influenza B lineages in Kenya matched the vaccine strain component of the corresponding season (based on Northern Hemisphere [October–March] and Southern Hemisphere [April–September] vaccine availability). Results: From 2012 to 2016, influenza B represented 31% of all influenza-associated ARIs detected (annual range, 13–61%). Rates of influenza B hospitalization and outpatient visits were higher for <5 vs ≥5 years. Among <5 years, B/Victoria was associated with pneumonia hospitalization (64% vs 44%; P = .010) and in-hospital mortality (6% vs 0%; P = .042) compared with B/Yamagata, although the mean annual hospitalization rate for B/Victoria was comparable to that estimated for B/Yamagata. The 2 lineages co-circulated, and there were mismatches with available trivalent influenza vaccines in 2/9 seasons assessed. Conclusions: Influenza B causes substantial burden in Kenya, particularly among children aged <5 years, in whom B/Victoria may be associated with increased severity. Our findings suggest a benefit from including both lineages when considering influenza vaccination in Kenya.